Electrochemotherapy, Electrogenetherapy, and Transdermal Drug Delivery Electrically Mediated Delivery of Molecules to Cells - Jaroszeski, Mark J.; Jaroszeski, Mark J. (Methods in Molecular Medicine,, 2000)
In Electrochemotherapy, Electrogenetherapy, and Transdermal Drug Delivery, leading experts comprehensively review all aspects of the delivery of therapeutic molecules to cells using electrical impulses-i.e., the extraordinarily promising new areas of electrogene therapy, electrochemotherapy, and transdermal drug delivery. Their survey ranges from outlines of the basic physical principles that govern cell permeabilization by pulsed electric fields, to descriptions of the current state-of-the-art in instrumentation and electrodes, to summaries of preclinical and clinical trial results. The authors focus on drug, gene, and transdermal delivery techniques, providing detailed examples of drug delivery using electric fields from a variety of pulse generators and electrodes. The protocols cover almost every variation in procedure and/or apparatus so that investigators can readily identify the method needed for their own work, or adapt one to their particular purposes. Comprehensive and authoritative, Electrochemotherapy, Electrogenetherapy, and Transdermal Drug Delivery provides entré to an immensely practical set of in vivo electroporation techniques, including electrogene therapy, electrochemotherapy, and transdermal drug delivery-techniques holding great promise for all those working toward better therapies for in cancer, metabolic diseases, and vaccination.